As escrevivências de professoras negras na educação básica: um estudo sobre identidade e representatividade em Tanquinho-Ba - Jesus, Juliana Soares de (2023)
The text presents a discussion about the writings of black teachers of Basic Education in the city of Tanquinho-BA, from the experiences of their body-territory and territory-place regarding ethnic-racial relations and addresses the political and representative possibility of these women as an act of insurgencies for a decolonial pedagogy. This is a qualitative research anchored in a decolonial pedagogy with theoretical ballast of black epistemology referenced by the authors: Conceição Evaristo, Neusa Santos, Muniz Sodré, Boaventura de Souza Santos, Nilma Lino Gomes, Sueli Carneiro, Bell Hooks, Anibal Quijano. The afromethodological route points to the writings of black teachers as an anti-racist methodological theoretical contribution committed to the condition of black women in a society crossed by racism, with identities forged in patterns of power, being, knowledge and territorialization